Amino acid composition of tropical fruits and vegetables I. Papaya (Carica papaya L.), bottle gourd (Lagenaria siceraria Standl.), swamp cabbage (Ipomea aquatica Forsk) and tomato (Lycopersion esculentum Miller) - Calonzo, Anna Theresa C
ABSTRACT The edible portion of 4 tropical fruit and vegetables, namely papaya (Carica papaya L.), bottle gourd (Lagenaria siceraria StandI.), swamp cabbage (Ipomea aquatica Forsk), and tomato (Lycopersion esculentum Miller), were analyzed for proximate and amino acid composition. The proximate composition of papaya was 87.36% moisture, 0.56% ash and 0.59% protein; that of bottle gourd was 95.77% moisture, 0.28% ash and 0.37% protein; that of swamp cabbage was 87.93% moisture, 0.84% ash and 4.95% protein; while that of tomato was 93.61% moisture, 0.32% ash and 1.23% protein. Among the 4 samples, bottle gourd has the highest moisture value, while the swamp cabbage obtained the highest value for both ash and protein. Among the amino acids, glutamic acid was recognized to have obtained generally the highest concentration in all 4 samples examined. Aspartic acid, threonine, serine, proline, alanine, valine and arginine were also present in relatively large amounts in certain fruit and vegetables. The glutamic acid content obtained by papaya was 8.65 mg %, while 19.71 mg % for bottle gourd, 11.32 mg % for swamp cabbage and 9.95 mg % for tomato. Bottle gourd generally showed to have the highest glutamic acid value and was also found to contain more of the non-essential amino acid than the rest of the samples. Papaya on the other hand, contain more of the essential amino acids but, it has the least glutamic acid value.